The Surprising Place : Stories - McCollum, Malinda (Book collections on Project MUSE., 2018)
"A woman walks a raccoon on a leash, a synchronized swimming coach pops pills during practice, a bagpiper holds a young girl hostage, and an orphan puts her fist through a window, discovering in the engine noise of a jet passing overhead the perfect witness to her inner pain. In this debut collection from prizewinning short story writer Malinda McCollum, people adrift in the American Midwest struggle to find their way in the world, with few signposts for guidance. Set largely in Des Moines, Iowa, over the expanse of several decades, these twelve stories explore the surprising places where our outsized longings may lead us. In prose as lean and unflinching as an Iowa winter, these stories offer confrontation and consolation in equal measure."--